Identification and determination of some fatty acid compounds and free phenolics from the seeds of Cuminum cyminum L. plant growing in Iraq - Hammad, Zainab N.; Khorsheed, Ayad C. (Journal of Kerbala for Agricultural Sciences, 2022)
The current research aims at the separation and identification of many fatty acid compounds from the seeds of cuminum cyminum L. that are grown in Iraq using a continuous soxhelt extractor and sequence solvent systems depending on the polarity, Pet-ether extract (CUI), chloroform extract (CU2), ethyl acetate extract (CU3) and ethanolic extract (CU4). Hot aqueous extracts (CU5) and saponification processes were also used to liberate the free pool of fatty acid compounds; (Palmatic, stearic, Linoleic, α - Linolenic and Oleic acids). The increasing of concentration of fatty acids was cleared from CU5à CU1 as a result of decreasing of the polarity. In addition to that, the extracts (CU3, Cu4 and Cu5) were carried out by the acid hydrolysis to obtain the free phenolic compounds, which were identified by means of using HPLC technique. The phenolic compounds, which were presented in the seeds of Cuminum cyminum L. were: (Apigenin, Gallic acid, Syringic acid, Vanillic acid, Rutin, Quercetin, Kaempferol and P-coumaric acid .Apigenin, Gallic acid and Syringic acid were appeared in the extracts (CU3, CU4 and CU5). Moreover, the Vanillic acid compound was presented in CU3 and CU4, Rutin and Quercetin were also presented in CU3 and CU5. Also the Kaempferol, it was presented only in CU4. Finally, P-Coumaric acid was identified only in CU5.